Análise do resfriamento distrital - Brandão, Rafael Cardoso (2018)
Unlike other studies, this survey intends to analyze a district cooling system through the exergoeconomic perspective, giving the chilled water stream a levelized cost per unit of exergy and comparing it with another costing methodology. It considers the implementation of this centralized cooling supply into the climatic environment of Rio de Janeiro as a solution to meet a commercial center demand. The absorption chillers heat source is saturated steam, coming from a heat recovery steam generator which receives flue gas rejected by a gas turbine. All the plant operates following the thermal load. This research covers this requirement along the whole year, approaching dynamic data by steady-state intervals. During the calculation process, an exergy analysis is carried out, exposing the components inefficiencies and their impact on the product cost. Additionally, auxiliary relations between the distribution network streams prices were developed in order to define their specific costs. The chiller simulation was boosted by IPSEpro® 6.0. Finally, this project certifies the exergoeconomy relevance, when applied to district cooling systems, due to its concern about the potential differences between several energy sources.